Produção de esporos, densidade do inóculo e caracterização de genótipos de trigo para resistência à mancha amarela, causada por pyrenophora tritici-repentis - Moschen, Franciely (2008)
Tan spot of wheat (Triticum aestivum), incited by Drechslera tritici-repentis is a disease economically important in several wheat growing areas of Brasil, under minimum tillage cropping system. Drechslera tritici-repentis, the causal agent of tan spot is a potentially destructive pathogen to wheat crop. The disease management has been done by fungicide spraying associated with genetic resistance of wheat varieties. Yield losses up to 40 to 60% of potential yield of wheat are reported in Brazil. The best way to control the disease is the use of resistant varieties, however, due to the occurrence of a complex of leaf spots on wheat, it is very difficult to introduce genetic resistance to all causal agents, and besides that little is known about the inheritance of resistance to D. tritici-repentis among wheat germoplasm. The objective of this work was to establish forms of producing and the density of inoculum of the pathogen ideal for characterizing wheat germplasm belonging to the Embrapa Trigo Germplasm Bank, searching for tan spot resistance. Severity and disease reaction were evaluated on varieties and breeding lines from one the Historic collection of wheat developed in different decades (1930 to 2005), on double haploids lines, and on genotypes of synthetic wheat, under controlled conditions and field, artificially inoculated with the pathogen. It was detected significant spore production of the fungus on the substrate based on V8 juice under stress of the mycelium followed by alternance of light/dark during 24 hours and under alternance of temperature. The best differentiation of genotype occurred with inoculum concentration of 6 to 9 thousand spores per mL. There were a great number of susceptible genotypes among tested material, besides considerable difference between seedling and adult plant reaction for the majority of genotypes tested. It was also noticed the necessity of evaluate the germplasm for a great number of isolates.